Are triphalangeal thumb-polysyndactyly syndrome (TPTPS) and tibial hemimelia-polysyndactyly-triphalangeal thumb syndrome (THPTTS) identical? A father with TPTPS and his daughter with THPTTS in a Thai family - Kantaputra PN. (2014)
We report on a Thai man who had triphalangeal thumb-polysyndactyly syndrome (TPTPS, MIM *190605) and his daughter who had tibial hemimelia-polysyndactyly-triphalangeal thumb syndrome (THPTTS, MIM *188770). The father had polysyndactyly of triphalangeal thumbs, syndactyly of fingers, duplicated distal phalanx of the left great toe, brachymesophalangy of toes, and the absence of middle phalanges of some toes. He was diagnosed as having TPTPS. His daughter was more severely affected, having complete syndactyly of five-fingered hands in rosebud fashion (Haas-type syndactyly), hypoplastic tibiae, absent patellae, thick and displaced fibulae, preaxial polysyndactyly of triphalangeal toes, and cutaneous syndactyly of some toes, the manifestations being consistent with THPTTS. Having two different syndromes in the same family suggests that they are actually the same disorder. A literature survey showed that there have been several families where THPTTS occurred with TPTPS or Haas-type syndactyly (and/or preaxial polydactyly type 2, PPD2). In addition, all loci for TPTPS, THPTTS, and PPD2 (and/or PPD3) have been assigned to chromosome band 7q36. These findings support our conclusion that TPTPS, PPD2 (and/or PPD3), and Haas-type syndactyly are a single genetic en-tity (THPTTS). We propose to call the condition "tibial hemimelia-polysyndactyly-triphalangeal thumbs syndrome."